2021
DOI: 10.3171/2021.2.focus201059
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of charged-particle therapy for chordomas and sarcomas of the mobile spine and sacrum

Abstract: OBJECTIVE Long-term local control in patients with primary chordoma and sarcoma of the spine and sacrum is increasingly reliant upon en bloc resection with negative margins. At many institutions, adjuvant radiation is recommended; definitive radiation is also recommended for the treatment of unresectable tumors. Because of the high off-target radiation toxicities associated with conventional radiotherapy, there has been growing interest in the use of proton and heavy-ion therapies. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…One such study, published in 2019, reported an 89.9% five-year local recurrence-free survival rate for patients receiving stereotactic radiosurgery in the form of 24 Gy in a single fraction for primary sacral or mobile spine chordoma 78 . A recent systematic review of definitive charged particle therapy found five-year local control rates of 56% to 68% for protons alone, 62% to 85% for mixed proton/photon therapy, and 53% to 100% for carbon ion radiotherapy 79 …”
Section: Malignant Tumorsmentioning
confidence: 99%
“…One such study, published in 2019, reported an 89.9% five-year local recurrence-free survival rate for patients receiving stereotactic radiosurgery in the form of 24 Gy in a single fraction for primary sacral or mobile spine chordoma 78 . A recent systematic review of definitive charged particle therapy found five-year local control rates of 56% to 68% for protons alone, 62% to 85% for mixed proton/photon therapy, and 53% to 100% for carbon ion radiotherapy 79 …”
Section: Malignant Tumorsmentioning
confidence: 99%
“…Despite these encouraging preliminary studies, the overall data of proton and carbon ion RT are quite limited. The superiority of these modalities in the definitive or adjuvant setting has not been demonstrated by systematic reviews, with charged particle therapy offering similar local control to modern photon therapy in the adjuvant setting 78 . In addition, access to proton beam therapy in the United States is still limited and typically only available in large metropolitan areas.…”
Section: Radiotherapymentioning
confidence: 99%
“…Houdek et al examined 193 patients with primary sacrococcygeal chordomas and found no improvement of oncologic outcomes with the addition of low-dose RT to en bloc resection, but rather was associated with an increased risk of local complications 71 . However, recent innovations in radiation modalities and charged particle therapy have improved delivery precision and efficacy while minimizing toxicity 66,67,[72][73][74][75][76][77][78][79][80] .…”
Section: Radiotherapymentioning
confidence: 99%
“…Der Vorteil der Partikeltherapie besteht darin, dass mit Abgabe der Energie im Zielbereich, die umgebenden Strukturen geschont werden. Ein systematisches Review zeigt keinen relevanten Unterschied zwischen verschiedenen Partikeln und kann bei Verwendung einer Partikeltherapie als primäre Behandlung und historischen chirurgischen Kohorten vergleichbar sein [28]. Eine Carbon-Ionentherapie kann auch für Patienten mit Resektionsrand-positiven Resektionen verwendet werden und könnte im Vergleich zu Photontherapie einen Vorteil haben [29].…”
Section: Strahlentherapieunclassified